2016
DOI: 10.3174/ajnr.a4862
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thrombectomy in Patients with Acute Ischemic Stroke and Lower NIHSS Scores: Recanalization Rates, Periprocedural Complications, and Clinical Outcome

Abstract: The clinical outcome of patients undergoing mechanical thrombectomy for acute ischemic stroke with mild stroke due to large-vessel occlusion appears to be predominately favorable, even in a prolonged time window. However, although infrequent, angiographic complications could impair clinical outcome. Future randomized controlled trials should assess the benefit compared with the best medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 30 publications
9
29
0
Order By: Relevance
“…One previous study with a relatively small sample size ( n = 33) has already shown that clinical outcome is predominately favourable for minor stroke patients having undergone MT, and our present results are in line with this study [21]. …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…One previous study with a relatively small sample size ( n = 33) has already shown that clinical outcome is predominately favourable for minor stroke patients having undergone MT, and our present results are in line with this study [21]. …”
Section: Discussionsupporting
confidence: 83%
“…Indeed, in our study, excellent and favourable outcomes were achieved in 65.0 and 78.3% of patients, respectively, versus 42.4 and 63.6% in the study cited above [21]. Our patients achieved less excellent and favourable outcomes than described in a recent multicentre study, showing that both excellent and good outcomes (77 and 89% respectively) could be achieved in minor stroke patients undergoing optimal medical management [7].…”
Section: Discussionmentioning
confidence: 48%
“…Patients with lower NIHSS scores on admission are known to have a better clinical outcome at 90 days, amounting to 63% in patients presenting with an initial NIHSS of ≤8 [27]. This correlates with our results with only 4 patients (8%) in the ILVO group being severely disabled and a significantly lower mortality rate of 6.4%.…”
Section: Discussionsupporting
confidence: 80%
“…In our study, the overall rate of successful reperfusion (79.9%) is within the range of core-lab controlled results (58.7-88%) [18,19,20,21,22], yet lower than that in self-reported series with reperfusion rates up to 91% [2,3,13,15,16,24,25,26,27]. One putative explanation might be the blinded regrading of all digital subtraction angiography images according to the Cerebral Angiographic Revascularization Grading standards, thereby ensuring common operator-independent grading standards over time.…”
Section: Discussionmentioning
confidence: 88%
“…Pfaff et al, 20 and the 16.5% (any ICH) and 4.7% in Dargazanli et al and the ETIS Registry investigators' study. 21 Although there are differences between the above studies, such as patient eligibility and variable criteria, leading to different results, the overall tendency favors endovascular therapy in patients with MIS and LVO.…”
Section: Figurementioning
confidence: 89%